From Library Co-operation to Consortia: Comparing Experiences in the European Union with the Russian Federation - van Borm, Julien; Sokolova, Natalia (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
Copeter is one of the few Tempus/Tacis projects about consortium building: bringing libraries together in a consortium in order to achieve common goals. This article will attempt to answer three main questions: 1. What factors create good library co-operation? 2. What are the conditions for success? 3. Is the Copeter consortium fulfilling these requirements?